Public Interest in Mass Media: Consumer Rights Protection Issues Raised By Individuals as a Public Interest Case in Lithuanian Online Media - Matkevičienė, Renata; Stonkienė, Marija (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English]Public good is the basis of public interest that determines the (co)existence of the community as well as the society. The media and its role in civic society play a major role in defining public interest, and it helps in manifesting this public interest to various stakeholders. Likewise, the public’s need to know of the role of the media in the presentation, consideration and representation of the public interest is extremely important.The relevance of public interest to a society is related to meeting the needs of a society. Changes in the functions of media from a forth power or a watchdog, to a moderator of public discussions had drawn media’s attention to the need for an inquiry of public interest and discussions about it in the media.The aim of this article is to determine how public interest is presented in Lithuanian online media. This article analyzes the case of presenting the protection of the rights of heat consumers – as an interest of the public – in Lithuanian online media. This article discusses the concept of public interest, the role of the media in discussing the public interest, and, when choosing a specific public interest issue, investigates how the topic of public interest is presented in Lithuanian online media.The case of public interest raised by the representative of the society – P. Markevičius, a lawyer and member of the Žvėrynas district community in Vilnius, was selected for the case study. The case is connected with the protection of the heat consumers’ rights, as P. Markevičius had detected potential violations of consumer rights being done by Vilnius energija (the provider of heat services in Vilnius city). All publications made during the period of 2010–2012 found using the Google search engine with the keywords “P. Markevičius” and “Vilniaus energija” were selected for the case study; qualitative and quantitative content analyses were used.The case study of public interest manifested in 2010–2012 in Lithuanian online media shows that the representation of the “public interest” by the representatives of the media is understood only as a way of giving space to citizens to present their views and talk about the problems relevant to them. The case leads to some consideration that the public interest in the media and by media is mostly understood as a way of supporting active citizens by inviting them to discussions and providing time for presenting their arguments, as well the position statements of experts and officials, but without any specific journalistic investigations.The development of civil society makes it possible to assume that the raising of issues related to public interest have also made some changes in the media – there could be seen an aspiration to raise problematic issues and promote discussions. Such monitored changes in civil society encourage the continuation of the ongoing investigation of the issue how public interest is manifested in online media – social media in particular.
Keywords: public interest; mass media; media roles; public space; consumer rights protection; Lithuanian online media